Pengaruh Model Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Kelas X pada Pembelajaran Sejarah - Nur Fitri Anisa; Aisiah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
History learning at the high school level is often perceived by students as boring, resulting in low active engagement in the learning process and impacting less than optimal learning outcomes. This condition requires educators to implement a student-centered learning model that is able to encourage active learning activities. This study aims to determine the effect of using the discovery learning model on the history learning outcomes of high school students. The study used a quasi-experimental approach with a pretest–posttest control group design. The research subjects consisted of two groups, namely the experimental class using the discovery learning model and the control class using the direct learning model. The data collection technique was carried out through a learning outcome test in the form of 30 multiple-choice questions given at the pretest and posttest stages. Data were analyzed using an independent t-test at a significance level of 0.05. The results of the analysis showed that the Sig. value (2-tailed) was 0.000 <0.05, which means there is a significant difference in history learning outcomes between students who learned with the discovery learning model and students who learned with the direct learning model. Thus, it can be concluded that the application of the discovery learning model has a positive effect on improving the history learning outcomes of high school students.